Procedural Sedation & Analgesia by Ketamine-Propofol (Ketofol) And Ketamine-Diazepam Combination In Day Case Surgery - A Comparative Study (Journal of the Bangladesh Society of Anaesthesiologists, 2018)
Introduction: Traditionally Procedural Sedation and Analgesia (PSA) is provided by various drugsand its combinations with mixed effect regarding safety and efficacy.Objective: The aim of the study was to compare the combination of Ketamine & Propofol (Ketofol) andKetamine-Diazepam for PSA in day case surgery.Materials & Methods: This prospective study was carried out in CMH Dhaka on sixty patients equallydivided in two groups between the period of May 2015 to September 2015. Group I patients receivedInjection Ketamine 1mg/kg & Injection Propofol 1mg/kg combination while group II patients receivedInjection Ketamine 2mg/kg & Injection Diazepam 0.2mg/kg combination. Clinical parameters like pulserate, non invasive blood pressure (NIBP), percentage saturation of oxygen (SpO2) were monitored, recordedand analyzed. Recovery was assessed by Aldred Recovery Score (ARS) and compared between groups.Results: Rise of heart rate, systolic blood pressure (SBP), diastolic blood pressure (DBP) were statisticallysignificant in group II patients when compared to group I both during the procedure & recovery but riseof mean arterial pressure (MAP) was significant only during procedure. The recovery time in group IIpatients (24.7 ± 3.6 min) was significantly higher (29.7 ± 4.1 min) than group I patients. Side effects likeexcessive bronchial secretion and postoperative agitation were also significantly lesser in Ketofol group.Conclusion: Ketofol provides safer and more effective sedation and analgesia than Ketamine andDiazepam combination.JBSA 2018; 31(2): 75-82